Strength characteristics of recycled asphalt pavement aggregate based geopolymer concrete. (2023) - Preethi, J.; Deepak, P.; Nikhil, N.; Omkar, G.; Vidya, R.; Bhuvaneshwari, P.
Abstract: Present work involved the utilisation of Reclaimed Asphalt Pavement (RAP) as aggregate in geopolymer concrete. Bulk quantity of RAP is being dumped in landfills and cause damage to the environment. Preliminary experiments were conducted to ascertain the strength characteristics of geopolymer concrete by partially replacing Natural Coarse Aggregate (NCA) with RAP. The geopolymer mix was designed for the M40 grade. Totally 45 cubes (100 mm × 100 mm) were cast to ascertain the strength. The different mixes adopted were GC-0RAP (No replacement), GC-20RAP (20 % of NCA with RAP), GC-40RAP (40 % of NCA with RAP), GC-60RAP (60 % of NCA with RAP), and GC-80RAP (80 % of NCA with RAP). The cubes specimens were subjected to compression up to failure. Comparison of compressive strength shows a percentage reduction of 5.89 %, 8.73 %, 11.78 %, and 23.17 % for GC-20RAP, GC-40RAP, GC-60RAP, and GC-80RAP respectively, with respect to conventional mix. Percentage decrease in rate per unit volume of GC-20RAP, GC-40RAP, GC-60RAP, and GC-80RAP were 2.6 %, 6.5 %, 8.6 %, and 11.6 %, respectively, compared to conventional mix. Despite more cost reduction, GC-80RAP failed to attain the target mean strength. The optimum mix was fixed as GC-60RAP, which brought down the rate without compromising the strength characteristics. The replacement would encourage recycled material in construction works.